The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41539-021-00095-7
|View full text |Cite
|
Sign up to set email alerts
|

First-year students’ math anxiety predicts STEM avoidance and underperformance throughout university, independently of math ability

Abstract: Math anxiety is widely considered a potential barrier to success in STEM. Current thinking holds that math anxiety is directly linked to avoidance of and underperformance in STEM domains. However, past evidence supporting these claims is limited in important ways. Perhaps most crucially, it is possible that math anxiety predicts STEM outcomes merely as a proxy for poor math skills. Here, we tested the link between math anxiety and subsequent STEM outcomes by measuring math anxiety, math ability, and several co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 49 publications
3
70
0
1
Order By: Relevance
“…In most of the Western world, the issue of gender inequity in STEM fields is wellknown along with broader concerns regarding female students' shying away from or under-performing in courses involving computational knowledge and skills [8,9]. Countless studies have focused on uncovering the reasons for the unbalanced presence of women in STEM academic programs and professions and their under-performance concerning computational competency [10][11][12][13], in the hope that systematic interventions can be implemented, and, with time, rectify the status quo. The reasons uncovered [14] include external factors (e.g., institutional policies) and internal ones (e.g., attitudes), which may create the perfect storm responsible for women remaining under-represented in STEM fields as well as exhibiting, irrespective of the chosen field of study, lower computational competency than male students.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the Western world, the issue of gender inequity in STEM fields is wellknown along with broader concerns regarding female students' shying away from or under-performing in courses involving computational knowledge and skills [8,9]. Countless studies have focused on uncovering the reasons for the unbalanced presence of women in STEM academic programs and professions and their under-performance concerning computational competency [10][11][12][13], in the hope that systematic interventions can be implemented, and, with time, rectify the status quo. The reasons uncovered [14] include external factors (e.g., institutional policies) and internal ones (e.g., attitudes), which may create the perfect storm responsible for women remaining under-represented in STEM fields as well as exhibiting, irrespective of the chosen field of study, lower computational competency than male students.…”
Section: Introductionmentioning
confidence: 99%
“…One potentially promising avenue is to examine to what extent the association between the sibling group composition and girls' interest in STEM is rooted in the psychological realm. A growing body of literature has indicated that the underrepresentation of girls in STEM fields is due in part to psychological elements, such as their lower levels of confidence in their STEM specific competencies (Tellhed et al, 2017); their greater gender stigma consciousness and their gender-based rejection sensitivity, which leads them to perceive STEM academic environments as threatening (Casad et al, 2019); and their significantly higher levels of math anxiety, which directly affects their avoidance of STEM fields, regardless of their math abilities (Daker et al, 2021;Maloney et al, 2012). Our results suggest that girls from specific sibling group compositional backgrounds may be more prepared to thrive in STEM learning environments because of their early exposure to male-dominated group climates, or because they believe more strongly that girls can be competent in math, as modeled by an older sister with high math ability.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we use the math ability of the older siblings as a proxy for role modeling. Research has shown that math achievement is positively linked to pursuing a STEM career (Wang & Degol, 2017;Wang et al, 2015), although some scholars have pointed out that the relationship between having cognitive mathematical abilities and majoring in STEM is complex, and is likely contingent on an individual's other cognitive abilities and field-specific ability beliefs, or may even be insignificant when the person's occupational plans are taken into account (Daker et al, 2021;Wang & Degol, 2017;Weeden et al, 2020). Nonetheless, high achievement in math is generally considered a predictor of pursuing a STEM career (Wang & Degol, 2017).…”
Section: Role Modeling Perspective: Older Siblings' Math Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited widely throughout campus via flyers. It should be noted that these data analyzed here are part of a larger dataset used in other papers 2,34,35 . The theoretical questions, analyses, and reports addressed in this paper are original.…”
Section: Methodsmentioning
confidence: 99%